2016
DOI: 10.1088/1751-8113/49/43/431001
|View full text |Cite
|
Sign up to set email alerts
|

Quantum deformations andq-boson operators

Abstract: and was published as part of a series of Viewpoints celebrating 50 of the most influential papers published in the Journal of Physics series, which is celebrating its 50th anniversary.by Holstein and Primakoff [3] using nonpolynomial functions of the raising/lowering operators to the same ends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…An intimate connection between the gravitation and the existence of the fundamental length scale was proposed in [109]. The minimal length has found to exist in string theory [110], loop quantum gravity [111], path integral quantum gravity [112], special relativity [113], doubly special relativity [114], coherent states [22][23][24][25][26][27][28][115][116][117][118][119][120][121][122],, etc. Furthermore, some thought experiments [109] in the spirit of black hole physics suggest that any theory of quantum gravity must be equipped with a minimum length scale [123], due to the fact that the energy required to probe any region of space below the Plank length is greater than the energy required to create a mini black hole in that region of space.…”
Section: A Noncommutative Quantum Mechanicsmentioning
confidence: 99%
“…An intimate connection between the gravitation and the existence of the fundamental length scale was proposed in [109]. The minimal length has found to exist in string theory [110], loop quantum gravity [111], path integral quantum gravity [112], special relativity [113], doubly special relativity [114], coherent states [22][23][24][25][26][27][28][115][116][117][118][119][120][121][122],, etc. Furthermore, some thought experiments [109] in the spirit of black hole physics suggest that any theory of quantum gravity must be equipped with a minimum length scale [123], due to the fact that the energy required to probe any region of space below the Plank length is greater than the energy required to create a mini black hole in that region of space.…”
Section: A Noncommutative Quantum Mechanicsmentioning
confidence: 99%
“…An intimate connection between the gravitation and the existence of the fundamental length scale was proposed in [109]. The minimal length has found to exist in string theory [110], loop quantum gravity [111], path integral quantum gravity [112], special relativity [113], doubly special relativity [114], coherent states [22][23][24][25][26][27][28][115][116][117][118][119][120][121][122],, etc. Furthermore, some thought experiments [109] in the spirit of black hole physics suggest that any theory of quantum gravity must be equipped with a minimum length scale [123], due to the fact that the energy required to probe any region of space below the Plank length is greater than the energy required to create a mini black hole in that region of space.…”
Section: A Noncommutative Quantum Mechanicsmentioning
confidence: 99%
“…The q-deformation is also used to fit the theoretical results to the experimental ones in nuclear and atomic physics [48][49][50][51][52][53], and Sviratcheva et al revealed the significant role of q-deformation in understanding higherorder effects in the many-body interactions [54]. Various dynamic equations of NLSE type with q-deformed potentials have been proposed to model q-deformed processes in nuclear and atomic physics (see i.e.…”
Section: Introductionmentioning
confidence: 99%